Coronal microleakage for readymade and hand mixed temporary filling materials - Aledrissy, Hager Ibn Idriss; Abubakr, Neamat Hassan; Yahia, Nadia Ahmed; Ibrahim, Yahia Eltayib (Iranian Endodontic Journal, 2011)
INTRODUCTION: The purpose of this in vitro study was to evaluate the sealing ability of the readymade temporary filling and hand mixed materials by assessing coronal microleakage. MATERIALS & METHODS: Standardized access cavities were prepared in 80 intact human permanent premolar teeth. They were divided randomly into four experimental groups (n=20). The teeth were restored using one of the temporary materials including Cavisol, Litrak, Zinc phosphate cement, Zinconol (IRM). Thermocycling was applied on the specimens. Methylene blue dye was applied and penetration was evaluated under stereomicroscope. Grading of the microleakage pattern was from 1 to 3, with 3 providing the best seal. Results were analyzed using one-way ANOVA test (P < 0.05). RESULTS: Microleakage of Cavisol and Litrak samples achieved grade 3; whereas zinc phosphate cement and Zinconol samples absorbed the dye into the bulk of the materials. Cavisol was found to exhibit the best seal amongst the four tested materials followed by Litrak, zinc phosphate cement, and Zinconol. There was a statistically significant difference in the microleakage scores obtained between the materials (P < 0.01). CONCLUSION: Among the four materials tested, readymade temporary filling provided the best sealing ability over hand-mixed. This study emphasizes the importance of correct placement and sufficient thickness of temporary filling materials in endodontic access cavities to ensure a tight seal.